CORPORATE SOCIAL RESPONSIBILITY MANUFACTURING COMPANY IN INDONESIA - Saifi, Muhammad (Universitas Brawijaya, Indonesia, 2020)
Corporate Social Responsibility (CSR) is a form of corporate moral responsibility to its stakeholders. The impact of the company's operational results must be accountable as a form of social responsibility to the stakeholders. The implementation of Corporate Social Responsibility done by the company well provides benefits in increasing the value of the company in the eyes of investors which can also affect the company's financial performance. This research was conducted to determine and explain the effect of Corporate Social Responsibility on the value of the company and the company's financial performance and to know and explain the influence of the company's value on the company's financial performance. This study uses quantitative research types, namely explanatory research with approval, where this research was conducted on cement manufacturing companies listed on the Indonesia Stock Exchange from 2014 to 2018. The research sample was obtained using a purposive sample method so as many as 6 sample units were obtained and using panel data there were 30 units of analysis. The data analysis technique used in this study is PLS (Partial Least Square) using SmartPLS. The results of this study indicate that Corporate Social Responsibility has a significant and positive effect on firm value, Corporate Social Responsibility has an insignificant and negative effect on Financial Performance, and Corporate Value has an insignificant and positive effect on Financial Performance.